Regulation of the human HBA genes by KLF4 in erythroid cell lines - Marini, M. Giuseppina; Porcu, Loredana; Asunis, Isadora; Loi, M. Giuseppina; Ristaldi, M. Serafina; Porcu, Susanna; Ikuta, Tohru; Cao, Antonio; Moi, Paolo (British journal of haematology, 2010)
Summary KLF1/EKLF and related Krueppel‐like factors (KLFs) are variably implicated in the regulation of the HBB‐like globin genes. Prompted by the observation that four KLF sites are distributed in the human α‐globin gene (HBA) promoter, we investigated if KLFs could also act to modulate the expression of the HBA genes. Among the KLFs tested, only KLF4/GKLF bound specifically to three out of four α‐globin KLF sites. The occupancy of the same sites by KLF4 in vivo was confirmed by chromatin immunoprecipitation assays with KLF4‐specific antibodies. In luciferase reporter assays in MEL cells, high levels of the wild type HBA promoter, but not mutated promoters bearing point mutations that disrupted KLF4‐DNA binding, were transactivated by over‐expression of KLF4. In K562 cells, induced KLF4 expression with a Tet‐off regulated cassette stimulated the expression of the endogenous HBA genes. In a complementary assay in the same cell line, knocking down KLF4 with lentiviral delivered sh‐RNAs caused a parallel decrease in the transcription of the HBA genes. All experiments combined support a regulatory role of KLF4 in the control of HBA gene expression.